PHYSICS TEACHING METHODS IN A MODERN SCHOOL (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article is devoted to new approaches and methods of teaching physics in a modern school. Information technologies increase the information content of the lesson, the effectiveness of teaching, give the lesson dynamism and expressiveness.